The Relationship Between Husband’s Support and Self-Adaptation of Primigravida Pregnant Women in Alas Rajah Village Blega District Bangkalan Regency - Wilujeng, Sri; Diana, Wulan; Khatijah, Siti (STIKES Adi Husada, 2024)
Pregnancy is a physiological and normal process, which is not only related to the biological aspect but also related to the social, cultural, psychological, emotional, and spiritual aspects of a woman’s life. Support is one of the important things to build coping mechanisms for self-adaptation in accepting conditions in pregnant women. The research aimed to determine the relationship between the husband’s support and self-adaptation of primigravida pregnant women. The research design was a cross-sectional approach. The independent variable was the husband’s support and the dependent variable was the self-adaptation of primigravida pregnant women. The population is primigravida pregnant women in Alas Rajah Village, Blega District, Bangkalan Regency. It is 47 with a sample of 42 pregnant women using probability sampling with a random sampling technique. The data collection technique used questionnaires. The statistical test uses the Spearman rank test with (a≤ 0.05). The research results showed that 24 people (57.1%) showed good husband support and 19 people (45.2%) showed good self-adaptation of primigravida pregnant women. The results of the Spearman test, the value p=0.000, means that there is a relationship between husband’s support and self-adaptation of primigravida pregnant women, with a correlation coefficient of 0.774, it means the level of strong relationship between husband’s support and self-adaptation in primigravida pregnant women. It is recommended that husbands provide full support so that the pregnant women feel they get the attention and therefore they can adapt to pregnancy conditions. This will have a positive impact on the continuity of the pregnancy.